'Why wait for the Blitz', 1941 (1941)
1941 1939-1945 "'Why wait for the Blitz', 1941" [hfr0202a], 1941 'Why wait for the Blitz' was the ninth Technical Report from the Association of Architects, Surveyors and Technical Assistants, a TUC affiliated union. The report is critical of A.R.P. [Air Raid Precautions] schemes for shelters, emergency accommodation and feeding and other Government measures for evacuation, billeting and rehousing following bombing raids.